2001
DOI: 10.1093/emboj/20.3.589
|View full text |Cite
|
Sign up to set email alerts
|

AtSPO11-1 is necessary for efficient meiotic recombination in plants

Abstract: The Saccharomyces cerevisiae Spo11 protein catalyses DNA double-strand breaks (DSBs) that initiate meiotic recombination. The model plant Arabidopsis thaliana possesses at least three SPO11 homologues. T-DNA and ethyl-methane sulfonate mutagenesis allowed us to show that meiotic progression is altered in plants in which the AtSPO11-1 gene is disrupted. Both male and female meiocytes formed very few bivalents. Furthermore, no fully synapsed chromosomes were observed during prophase I. Later, in meiosis I, we ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
544
5
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(574 citation statements)
references
References 71 publications
(124 reference statements)
24
544
5
1
Order By: Relevance
“…In contrast to the case of atxrcc3/ spo11-1, no chromosome fragmentation is observed in anaphase II of the atrad51/atspo11-1 double mutant (Li et al, 2004). Grelon et al (2001) reported the presence of bridges in anaphase I of the spo11-1 mutant but no bridges in anaphase II. These observations suggest that AtXrcc3, and presumably also AtRad51C, functions in a post-AtRad51 role in the repair Spo11-induced DSBs or DSBs in homologous chromosomes and sister chromatids damaged spontaneously or by a minor meiotic endonuclease other than Spo11.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In contrast to the case of atxrcc3/ spo11-1, no chromosome fragmentation is observed in anaphase II of the atrad51/atspo11-1 double mutant (Li et al, 2004). Grelon et al (2001) reported the presence of bridges in anaphase I of the spo11-1 mutant but no bridges in anaphase II. These observations suggest that AtXrcc3, and presumably also AtRad51C, functions in a post-AtRad51 role in the repair Spo11-induced DSBs or DSBs in homologous chromosomes and sister chromatids damaged spontaneously or by a minor meiotic endonuclease other than Spo11.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, Forget et al (2004) showed the localization of Xrcc3 at sites of DNA breaks within 10 min after exposure to g-irradiation and that such localization is independent of Rad51. In plants, meiosis is initiated by the formation of DSB, which is introduced by Spo11, in a manner similar to that in yeast (Grelon et al, 2001;Li et al, 2004). Further studies should be performed to determine the localization of AtRad51C and AtXrcc3 following DSB formation by Spo11 in meiosis to understand the function of AtRad51C and AtXrcc3 in HR.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a Mre11 mutant (the mre11-1 allele, truncated after amino acid 261, in the phosphoesterase motif IV) is viable, but sterile (Bundock & Hooykaas 2002). These mutants show no normal pachytene stage and a defect in homologous chromosome pairing and synapsis, and extensive meiotic chromosome fragmentation (Bleuyard et al 2004, Puizina et al 2004, which is not seen in a spo11 mutant (Grelon et al 2001). In addition, the fact that this fragmentation in mre11 mutant is Spo11-dependent clearly suggests that DSB are formed by Spo11 in the Arabidopsis Mre11 complex mutants, but that they are not repaired (Puizina et al 2004).…”
Section: Conservation Of the Roles Of The Mre11 Complex For Meiotic Rmentioning
confidence: 99%
“…Mutation in the Arabidopsis AtSPO11-1 gene shows abnormalities similar to those of the yeast spo11 mutants, including greatly reduced recombination and synapsis. However, the presence of residual bivalents indicates that there might be SPO11-independent pairing, synapsis, and/or recombination mechanisms [45].…”
Section: Resolution Of Dhjmentioning
confidence: 99%